2015
DOI: 10.1371/journal.pone.0122899
|View full text |Cite
|
Sign up to set email alerts
|

Association of Individual Non-Steroidal Anti-Inflammatory Drugs and Chronic Kidney Disease: A Population-Based Case Control Study

Abstract: BackgroundNon-steroidal anti-inflammatory agents (NSAIDs) are known to be associated with renal damage. No clear evidence exists regarding differential risk of chronic kidney disease (CKD), specifically, across various NSAIDs.AimThe aim of this population-based case-control study was to evaluate the association between use of individual NSAIDs and risk of CKD in a general population of Southern Italy.MethodsA nested case-control study was carried out using the general practice Arianna database, identifying inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 41 publications
4
41
0
8
Order By: Relevance
“…18 Large epidemiological studies of healthy individuals have not consistently demonstrated an association between chronic non-aspirin NSAID use and CKD. 1922 In contrast, high-risk individuals, such as the elderly, have a more rapid decline in estimated glomerular filtration rate (eGFR) after exposure to high doses of non-aspirin NSAIDs, 23 which was supported by other small cohort and case-control studies. 24 Non-aspirin NSAIDs can also reduce sodium excretion, increase intravascular volume, and increase systolic blood pressure by approximately 5 mmHg on average in a meta-analysis.…”
Section: Commentmentioning
confidence: 94%
“…18 Large epidemiological studies of healthy individuals have not consistently demonstrated an association between chronic non-aspirin NSAID use and CKD. 1922 In contrast, high-risk individuals, such as the elderly, have a more rapid decline in estimated glomerular filtration rate (eGFR) after exposure to high doses of non-aspirin NSAIDs, 23 which was supported by other small cohort and case-control studies. 24 Non-aspirin NSAIDs can also reduce sodium excretion, increase intravascular volume, and increase systolic blood pressure by approximately 5 mmHg on average in a meta-analysis.…”
Section: Commentmentioning
confidence: 94%
“…Regular ibuprofen users in the NHANES had no change in renal function compared with controls. 29) There was also no link demonstrated in the case control study by Ibanez et al34) nor the large 14 year prospective study by Rexrode et al32) In a recent Italian case control study of approximately 2,000 patients with CKD and nearly 8,000 matched controls, no association was identified between high intake of NSAIDs and renal insufficiency (OR, 0.94; 95% CI, 0.84 to 1.05) 39). A multicenter European report of 4,529 dialysis patients and controls did not find abuse of any common non-phenacetin analgesics to increase the risk of ESRF (OR, 1.02; 95% CI, 0.81 to 1.28) 40).…”
Section: Non-steroidal Anti-inflammatoriesmentioning
confidence: 95%
“…Изве-стно, что при ревматических заболеваниях имеется по-вышенный риск развития осложнений со стороны ЖКТ, ССС и почек, в том числе и вне зависимости от получаемого лечения [39][40][41][42][43][44][45][46][47]. Существующие на дан-ный момент шкалы не способны учитывать вклад вос-паления в повышение соответствующих рисков.…”
Section: мониторинг безопасности после начала лечения нпвп при нunclassified